(untitled) - Abram, David (New York, 1996)
Counter Animal tracks, word magic, the speech of stones, the power of letters, and the taste of the wind all figure prominently in this intellectual tour de force that returns us to our senses and to the sensuous terrain that sustains us. This is a major work of ecological philosophy that startles the senses out of habitual ways of perception.
Keywords: Philosophy of nature,Body, Human (Philosophy),Perception (Philosophy),Human ecology,Khoa học tự nhiên